EPIDEMIOLOGICAL STUDY OF RABIES TRANSMITTING ANIMAL BITE (RTAB) IN KENDARI CITY IN 2024 - Irma Irma (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2026)
Rabies has spread throughout the world and causes more than 55,000 deaths each year. In Indonesia, of the 38 provinces, 26 provinces have been identified as endemic areas for rabies. Southeast Sulewesi is one of the provinces where rabies is endemic with cases continuing to increase every year and by 2025 there will be 1337 GHPR cases and Kendari City will be one of the areas with the most GHPR cases. This research is descriptive research with a descriptive epidemiological approach. This research was conducted on 1 – 14 February 2026 in Kendari City, Southeast Sulawesi Province. The population of this study was 224 patients who experienced animal bites that transmit rabies (GHPR). All sufferers who experienced GHPR participated as samples in this study. The sampling technique was carried out using a non-random sampling technique, namely the total sample. Data collection using surveys and interviews. The data that has been collected is then analyzed univariately and presented in the form of tables and graphs accompanied by narrative. From the research results, it can be concluded that the majority of GHPR cases occur in the 16-44 year age group and most of them are male. GHPR cases in Kendari City in 2024 with the highest incidence occurring in October, January and June, while the lowest GHPR cases occurred in March.